The European Union’s Conflict Of Law Rules Governing Contract Law: A Re-Evaluation In The 21st Century - Hakki, Murat M. (Journal of Malaysian and Comparative Law, 2002)
At the beginning of the twentieh centure the commercial law of the Philippines, which had come to embody a synthesis of the Spanish civil law and United States (hereafter 'US') common law, was heralded as one of the most modern and progressive systems of law in the Asian region. One example of the early infusion of US common law can be found in the field of law governing security over personal property, where new security instruments were introduced by the then US Administration of the Philippines.